2001
DOI: 10.1177/104063870101300102
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Immunohistochemical Detection of DifferentHelicobacterSpecies in the Gastric Mucosa of Cats

Abstract: Abstract. Detailed histopathological evaluation of the gastric mucosa of Helicobacter-infected cats is complicated by the difficulty of recognizing Helicobacter organisms on hematoxylin and eosin (HE)-stained sections and the ability of multiple Helicobacter species to infect cats. In this study, the presence and localization of different species of Helicobacter in the stomachs of cats was investigated using silver staining and immunohistochemistry. Five groups containing 5 cats each were established (group 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 85 publications
(131 reference statements)
3
27
0
Order By: Relevance
“…15 The failure of amplification in these cases may also be because of the lack of adequate numbers of organism in the sections used for PCR analysis. Alternatively, immunohistochemical methods are known to cross react with other Helicobacter species, 16,17 and these findings may represent infection with Helicobacter organisms other than H. pylori. The primer and probe combinations used in this study have been previously shown to be specific for H. pylori, 12 which raises the possibility of false-positive immunohistochemistry results due to cross reactivity with an expected lack of detection by PCR.…”
Section: Assay Performancementioning
confidence: 99%
“…15 The failure of amplification in these cases may also be because of the lack of adequate numbers of organism in the sections used for PCR analysis. Alternatively, immunohistochemical methods are known to cross react with other Helicobacter species, 16,17 and these findings may represent infection with Helicobacter organisms other than H. pylori. The primer and probe combinations used in this study have been previously shown to be specific for H. pylori, 12 which raises the possibility of false-positive immunohistochemistry results due to cross reactivity with an expected lack of detection by PCR.…”
Section: Assay Performancementioning
confidence: 99%
“…This antibody was shown to detect H. suis, H. heilmanni and H. felis (De Groote et al, 2000;Scanziani et al, 2001). As control, an additional section was incubated in a similar manner with an irrelevant rabbit serum.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…However, follicular organization of the inflammatory cells was restricted to the infected animals (193,204).…”
mentioning
confidence: 99%